Treatment adherence and subjective well-being in HIV/AIDS infection - Ana Catarina Rodrigues da Silva Reis (2013)
The aim of this study was to analyze the relationship between treatment adherence and subjective well-being (positive and negative affects and satisfaction with life) in HIV/AIDS infection. The empirical study was conducted at two Portuguese hospitals (Porto and Lisbon) with a sample of 197 outpatients diagnosed with HIV/AIDS attending the Infectology service and on antiretroviral medication, during a 6-month period (February-July 2009). All patients were asked for voluntary fulfillment of the questionnaire which recorded information on different socio-demographic variables. Clinical records were inspected in order to collect additional clinical information from the patients. The